Prevalence of dermatophytosis among Suse federal prison inmates using conventional identification methods and PCR-RFLP typing - Mohammed, Saman M.; Al-Jaff, Bahrouz M. A. (Sulaimani Journal for Pure and Applied Sciences, 2020)
Dermatophytosis is a common skin infection especially in closed area with high temperature and humidity. Prisons are considered as closed areas especially for long times existed inmates in addition to some risk factors that may increase dermatophytosis. To investigate the prevalence and the risk factors of dermatophytosis in Suse federal prison for men at Sulaimani, northern Iraq, a total of 1620 inmates were clinically screened. Clinically suspected dermatophytosis by specialists were 139 (8.5%), they distributed on 102 (73%) Tinea pedis, 18 (12%) Tinea cruris, 14 (10%) Tinea corporis, 4 (3%) Onychomycosis, and 1 (0.7%) tinea mannum. By microscopical, cultural and PCR-RFLP typing procedures 50 cases were confirmed that distributed on 25 (50%) tinea pedis, 15 (30%) tinea cruris, 9 (18%) tinea corporis and 1 (2%) onychomycosis. The causative agents were Trichophyton rubrum 16 (32%), Trichophyton mentagrophytes and Trichophyton interdigitale 14 (28%) for each, Epidermophyton floccosum 4 (8%) and Trichophyton schoenleinii 2 (4%). Trichophyton interdigitale was the most frequently isolated from tinea pedis (40%), Trichophyton rubrum and Trichophyton mentagrophytes from tinea corporis (33% for each) and Trichophyton rubrum from onychomycosis and tinea cruris (%100 and 40% respectively). Antifungal administration and frequency of bathing were with significant effect on identification of the causative agent by direct KOH test (P= 0.000 and P= 0.026 respectively) and on its recovery by culture method (P= 0.000 and P= 0.016 respectively). The non-significant risk factors were age (P= 0.07), education level (P= 0.82), smoking (P= 0.61), and duration of imprison (P= 0.557). KOH exam was fast and cheap but it is less specific and sensitive. Culture method of identification is essential to identify species of dermatophytes, but it was time consuming and with problems related with confusion in dissemination between species morphologically that could be avoided by PCR-RFLP method which we consider it as a golden method for identification in spite of its high cost but it is with less time, correct identification, and highest sensitivity.
Keywords: Dermatophytes; Tinea; Prison; PCR-RFLP